2013
DOI: 10.1590/s1516-18462013005000011
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição dos fonoaudiólogos na atenção à saúde no estado de Minas Gerais entre 2005 e 2010

Abstract: OBJETIVO: analisar a tendência de distribuição dos fonoaudiólogos inseridos na atenção à saúde no estado de Minas Gerais no período de 2005 a 2010. MÉTODO: trata-se de um estudo retrospectivo, baseado na análise de banco de dados secundários de domínio público, os Cadernos de Informações de Saúde do Sistema de Informações em Saúde Brasileiro, o DATASUS. Foram analisados dados referentes aos 853 municípios do estado, destacando-se os indicadores de recursos relacionados ao número de profissionais de fonoaudiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
22

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 14 publications
1
12
0
22
Order By: Relevance
“…The rise of the number of respondents employed in public institutions, as observed in the present study, follows the expansion of speech-language therapists working in the national healthcare system (4,7) , observed since 1990 due to: the creation of the Brazilian Society of Speech Committee of Public Health (12) ; changes to the national curriculum guidelines for undergraduate courses in speech-language pathology, which now prioritize country's healthcare system (13) ; teamwork and attention to comprehensive health and the inclusion of speech-language therapy in services related to the Family Health Strategy (6) . And finally, regarding changes related to the workplace, it is noteworthy that the increase of respondents' activity in regular schools and a reduction of activity in special schools are linked to Brazilian educational policies that state the education of students with special educational needs (PNEEs) must occur in the regular school system.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The rise of the number of respondents employed in public institutions, as observed in the present study, follows the expansion of speech-language therapists working in the national healthcare system (4,7) , observed since 1990 due to: the creation of the Brazilian Society of Speech Committee of Public Health (12) ; changes to the national curriculum guidelines for undergraduate courses in speech-language pathology, which now prioritize country's healthcare system (13) ; teamwork and attention to comprehensive health and the inclusion of speech-language therapy in services related to the Family Health Strategy (6) . And finally, regarding changes related to the workplace, it is noteworthy that the increase of respondents' activity in regular schools and a reduction of activity in special schools are linked to Brazilian educational policies that state the education of students with special educational needs (PNEEs) must occur in the regular school system.…”
Section: Discussionsupporting
confidence: 52%
“…It is understood that bringing speech-language therapists closer to these diverse realities assumes that their initial and ongoing training must consider the guidelines contained in public health and education policies while providing support for the systematization of speech-language actions that consider the social determinants involved in professional activity (6,7,10,11) . Regarding the academic background of the respondents and their institution of origin, it was found that in 2000 and 2011, the majority of respondents had completed an undergraduate degree in speech-language pathology within the Board's jurisdiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is a State responsibility, access to public SLH services is limited in several locations around the country (5,6,7,8) , and does not meet the population's needs and demands, leading to the inadequate provision of care. Few studies have investigated SLH provision in SUS.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated SLH provision in SUS. Two have been conducted in Minas Gerais (7,8) , one in Bahia (5) and one in Pernambuco (6) , all using different approaches. The results suggest inter-regional differences and an insufficient number of SLH professionals to meet the population's needs, particularly in regions of low socio-economic status.…”
Section: Introductionmentioning
confidence: 99%